DIGITALIZATION OF FINANCIAL MANAGEMENT THROUGH TRAINING AND ASSISTANCE IN THE PREPARATION AND ANALYSIS OF COMPUTING SYSTEM-BASED FINANCIAL REPORTS FOR ISLAMIC BOARDING SCHOOL COOPERATIVES IN THE BLITAR DISTRICT - Fadia Zen; Achmad Murdiono; Lulu Nurul Istanti (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
The cottage boarding school serves as an Islamic educational institution focused on studying, comprehending, deepening, appreciating, and practicing the teachings of Islam, placing particular emphasis on instilling religious morals as daily behavioral guidelines. Moreover, these Islamic boarding schools, in their role as agents of change, not only contribute to religious and societal education but also actively participate in societal development and social transformation. Recognizing the pivotal role of cottage Islamic boarding schools in the community, especially in economic development, this study proposes the reinforcement of Islamic boarding school cooperatives (Kopontren) as economic driving forces within their environments. Initial observations highlight two key challenges: 1) Manual financial reporting based on outdated methods without utilizing SAK ETAP guidelines, and 2) The lack of financial performance analysis by Kopontren managers. The research commences with an introductory phase involving a literature review, followed by an in-depth exploration through secondary data analysis. Subsequently, an internal focus group discussion (FGD) is organized to gain insights into the actual cooperative conditions of cottage boarding schools. This FGD engages with the Department of Cooperatives and Micro, Small, and Medium Enterprises (MSMEs). To ensure the seamless progress of the activities, the execution team will coordinate with the District Cooperatives and MSMEs Service in Blitar, serving as a governmental institution officially supporting the establishment of cooperative cottage boarding schools.